200k views
2 votes
5/x+3 take away 1/x-2 equals to 1. solve two possible answers for x

1 Answer

4 votes

Answer:

Solution:-

  • First write the given equation


\qquad{:}\longrightarrow
\sf \frac {5}{x+3}-(1)/(x-2)=1


\qquad{:}\longrightarrow
\sf \frac {5 (x-2)-1 (x+3)}{(x+3)(x-2)}=1


\qquad{:}\longrightarrow
\sf \frac {5x-10-x }{x^2-6x-6} =1

  • use cross multiplication method


\qquad{:}\longrightarrow
\sf 5x-x-10=x^2-6x-6


\qquad{:}\longrightarrow
\sf x^2-6x-6=4x-10


\qquad{:}\longrightarrow
\sf x^2-6x-4x-6+10=0


\qquad{:}\longrightarrow
\sf x^2-10x+4=0

  • use quadratic formula


\qquad{:}\longrightarrow
\sf x=\frac {-b\underline{+}\sqrt {b^2-4ac}}{2a}


\qquad{:}\longrightarrow
\sf x=\frac {10\underline{+}\sqrt {(-10)^2-4×1×4}}{2×1}


\qquad{:}\longrightarrow
\sf x=\frac {10\underline{+}√(100-16)}{2}


\qquad{:}\longrightarrow
\sf x=\frac {10\underline{+}\sqrt {84}}{2}


\qquad{:}\longrightarrow
\sf x=\frac {10+\sqrt {84}}{2}\quad or\quad x=\frac {10-√(84)}{2}

User Solyd
by
6.5k points